ChemInform Abstract: Organic Synthesis Based on the Beckmann Fragmentation: Generation of an Electrophilic Salt Intermediate and Successive C—C Bond Formation Using Gilman Reagents. Issue 36 (September 2015) - Fujioka, Hiromichi; Matsumoto, Nao; Ohta, Reiya; Yamakawa, Maki; Shimizu, Nozomi; Kimura, Takashi; Murai, Kenichi
Abstract Various α‐alkoxy oximes are converted with collidine to form a collidinium salt intermediate, which reacts with cuprates (II) or (V) to give the corresponding nitriles.